Study on applicability of parallel perforated ventilation subgrade to the runway in frozen soil regions - Xiaolan Liu; Chuanwei Fu; Chao Lv (Alexandria Engineering Journal)
To maintain the stability of temperature and displacement of runway in frozen soil regions and ensure the safety of the aircraft taking off and landing, the runway with the parallel perforated ventilation subgrade is proposed. The numerical model of runway is established and verified by comparing with the air velocity field, temperature field, and displacement field in previous studies. Results show the parallel perforated ventilation subgrade is suitable for runway in frozen soil regions, and effectively reduce temperature and maintain stability of runway. The displacement of runway decreases rapidly after the subgrade is cooled by the parallel perforated ventilation for the first year, and tends to a fluctuated range of −2.5–0 mm after the tenth year. The maximum thawing settlement of runway appears on December 20th every year. The displacement of runway is increasing from the center of pavement to the natural surface, and the lateral inhomogeneous displacement between pavement and natural surface increases year by year. The annual maximum displacement in the center of pavement decreases rapidly in the first five years, then decreases slowly, and tends to fluctuate steadily after the seventeenth year. This study provides technical support for the design and construction, operation and maintenance of runway.